Competencies of diabetes educators in facilitating self-management and its associated factors among diabetic patients in Malaysia - Subramaniam, Umma Devi (2016)
Introduction : Diabetes Mellitus is emerging as an epidemic of the 21st century and threatens to overwhelm the health care system in the near future. There were nearly 1.5 million adults affected by the disease and there is an increment of about 3.3% in the prevalence of diabetes over the last decade in Malaysia. Self-management of diabetes among diabetic patients can be achieved through diabetes education provided by competent diabetes educators. Objectives : The aim of the study was to determine the diabetes educators’ competencies to facilitate self- management and its associated factors among diabetic patients in Malaysia. The specific objectives of this study were to determine the sociodemographic, service and training factors of diabetic educators, their knowledge on the five domains of competencies on the clinical understanding of diabetes management (Domain I), culturally-competent supportive care across the lifespan (Domain II), teaching and learning skills (Domian III), diabetes self-management practices (Domain IV), and health promotion and other programs (Domain V), and the challenges faced by them in counselling diabetic patients. Methodology : This was a cross-sectional study using a self-assessment questionnaire adapted from American Association of Diabetes Educators Guidelines (2013) with 445 diabetes educators randomly selected using simple random sampling in Primary and Secondary Healthcare Centres from five states in Malaysia. The reliability and validity of the questionnaire were done. Mean and standarad deviation were used to compute the competencies of diabetes educators’ on the five domains of competencies. Their level of competency was determined as Level 1 (low competency), Level 2 (moderate competency) and Level 3 (high competency). The study also described the challenges faced by the diabetes educators in their daily job. To test the significant association between the independent variables (socio-demographic, service and training factors factors) and dependent variable (level of competency), a Pearson Correlation test of association was used. Multiple linear regression was used to predict the variables of diabetes educators’ competency. Results : The findings of the study showed that mean value for the competency of the diabetes educators is 3.11± 0.44. The mean values for the Domain I was 3.35 ± 0.55, Domain II was 3.37 ± 0.54, Domain III was 2.69 ± 0.59, Domain IV was 3.21 ± 0.50 and Domain V was 2.91 ± 0.70. In terms of association between the independent and dependent variables, that there was a weak and negative association between age and competency. There was also weak and significantly positive association between the number of years as diabetes educator and competency. There were significant associations between gender, ethnicity, job position, academic qualification and type of post-basic course attended and their level of competency. The overall mean for the challenges faced by diabetes educators was at moderate level. Predictors of diabetes educators’ competency were gender, ethnicity, academic qualification and number of years as diabetes educators. Conclusion : The overall competency of the Malaysian diabetes educators was high at Level 3. Their competency was associated positively with gender, number of years as diabetes educators and type of post-basic course attended and negatively associated with age, ethnicity, job position and academic qualification. They were satisfied as their role was recognised by their superiors and they were given the empowerment to carry out the relevant programs related to the patients’ diabetes control.